Assessment of right ventricular remodeling in chronic thromboembolic pulmonary hypertension by 2D-speckle tracking echocardiography: A comparison with cardiac magnetic resonance - Wang, Yeqing; Guo, Dichen; Liu, Mingxi; Zhang, Xinyuan; Hu, Huimin; Yang, Hao; Yang, Yuanhua; Lv, Xiuzhang; Li, Yidan; Guo, Xiaojuan (Frontiers in Cardiovascular Medicine, 2022)
Background Right heart remodeling occurs in a substantial proportion of patients with chronic thromboembolic pulmonary hypertension (CTEPH) and significantly affects their prognosis. Two-dimensional speckle-tracking echocardiography (2D-STE) can be used to evaluate myocardial deformation under physiological and pathological conditions. This study aimed to assess the feasibility of 2D-STE for evaluating right ventricular (RV) remodeling in CTEPH patients. Methods This retrospective study included 21 CTEPH patients who underwent transthoracic echocardiography (TTE) and cardiac magnetic resonance (CMR). Data for the following parameters that can reflect RV function were collected: tricuspid annular plane systolic excursion (TAPSE), fractional area change (FAC), right ventricular index of myocardial performance (RIMP), peak systolic velocity of the tricuspid annulus (S'), and CMR-right ventricular ejection fraction (CMR-RVEF). The following strain parameters were calculated using post-processing software: STE-RV global longitudinal strain (STE-RVGLS), STE-RV free wall longitudinal strain (STE-RVFWLS), and CMR-RVGLS. Results As CMR-RVEF deteriorated, RV remodeling in CTEPH patients became more apparent and was mainly characterized by significant enlargement of the RV, weakening of myocardial deformation, and a decrease in RV contractility (RV area, STE-RVFWLS, STE-RVGLS: mild vs. severe and moderate vs. severe, p < 0.05; CMR-RVGLS: mild vs. severe, p < 0.05; TAPSE: moderate vs. severe, p < 0.05). Moreover, the Pearson correlation coefficient for correlation with CMR-derived RVEF was stronger for RVFWLS than for CMR-GLS (r-value: 0.70 vs. 0.68), and the strain values measured by 2D-STE showed a weak correlation with right heart catheterization data. Bland-Altman analysis showed good agreement between 2D-STE and CMR-feature tracking (FT) for RVGLS (bias = −0.96; 95% limit of agreement from −8.42 to 6.49). Conclusions For the measurement of RVGLS, 2D-STE is similarly feasible to CMR-FT and could sensitively identify right heart remodeling.